Récits écoféministes de voyages interstellaires : observer et créer de nouveaux mondes. - Clémence Mathieu (ReS Futurae)
The Ekumen cycle is a set of science-fiction books written between 1966 and 2002 by the american author Ursula le Guin. By telling stories of new worlds discoveries which reconsiders the mankind/nature, man/woman dualisms and dominations, the writer is involved in the creation of eco-feminist demands and ideas ; thus the Ekumen tales may qualify as eco-feminist fiction. The revelation of possible new worlds allows the setting-up of marginal groups during the second half of the 20th century, which establish themselves as critics of the modern age western world. The acknowledgement of the existence of other worlds in an elsewhere enables opportunities of imagining, then creating new worlds at the very core of the reality that one wishes to modify. Thus, the Ekumen eco-feminist fictions are regarded as generating new narratives offering the power to create the future or the present of the possible end of a certain world.